Sistem Informasi Akuntansi Omah Jenang Kelapa Sari Blitar - KRISTIANI, NOVA DEWI; KUSUMANINGTYAS, DIAN (Universitas Nusantara PGRI Kediri, 2020)
With the development of the UMKM business, it becomes a separate reason for researchers to find out the extent of the accounting system in Omah Jenang Kelapa Sari Blitar. Omah Jenang Kelapa Sari Blitar is one of the large MSMEs produced by jenang in the Kedamangan area, Blitar. In terms of its success, Omah Jenang Kelapa Sari depends on its sales output. This makes accounting information one of the important things to do in achieving the goals of a company. The research method used is qualitative research which is then described. The findings will be validated by the source triagulation method, which is to compare the existing findings with the relevant book sources. Based on the results of the interview, the researcher suggests adding a sales journal recording, making a sales flow chart, making a cash receipt journal recording.